Causes of and Modifiable Factors Contributing to Neonatal Deaths at Dora Nginza Hospital in the Eastern Cape, South Africa - Liesl Nieuwoudt MBChB, DCH (SA); Cheryl Anne Mackay FRACP PhD (UKZN); Siyazi Mda PhD, MMedPaed, MBChB (SAGE Publishing, 2022)
Dora Nginza Hospital (DNH) has a neonatal mortality rate higher than global and national averages. In 2015 to 2016 the neonatal mortality rate in South Africa was 18.1/1000 live births compared with 31.3/1000 live births at DNH. A retrospective study was conducted including neonates less than 28 days of life with a birth weight ≥500 g that demised in DNH neonatal unit. The NMR for the study period was 17.7/1000 live births. There were 101 (70.6%) early and 42 (29.4%) late neonatal deaths. Causes of death included infection (n = 47; 32.9%), immaturity-related (n = 42; 29.4%), congenital abnormalities (n = 26; 18.2%), hypoxia (n = 24; 16.8%) and other (n = 4; 2.8%). There were significant associations between cause of death and administrative-related factors ( P  < .01), health-personnel related factors ( P  < .001) and patient-related factors ( P  = .01). Key strategies to be implemented include improving infection prevention and control, appropriate resource allocation, improved attendance and quality of antenatal care, ongoing skills training, and interventions to maintain normothermia.